Clinical characteristics of pregnant women in labor with SARS-CoV-2 infection at high altitude: A case series - Collantes Cubas1,, Jorge Arturo (2020)
Introduction: Fewer COVID-19 cases and less lethality have been observed at high altitude compared to cases reported at sea level. There are currently no publications reporting clinical behavior of pregnant women with COVID-19 at high altitude. Methods: This is a retrospective study with review of medical records between March 6, 2020 and June 15, 2020. The first thirteen cases of pregnant women with COVID-19 who were attended at Simón Bolívar COVID-19 Hospital, located at 2750 meters above sea level, are described. The cases came from altitudes between 2 035 and 3 502 meters above sea level (masl). Statistical analysis used SPSS, version 19.0. Results: Thirteen cases of pregnant women with COVID-19 confirmed by IgM for SARS-CoV-2 were attended at 2 750 masl (9 022.31 feet) in the Peruvian Andes. Delivery by cesarean section occurred in eight cases (61.5%) and five (38.5%) delivered vaginally. There were two cases (15.4%) of preeclampsia, one with diagnosis of HELLP syndrome, prematurity and fetal death. Three cases (23.1%) developed uterine hypotonia that required Hayman or B-Lynch suture. Two cases (15.38%) were complicated with oligohydramnios and two with urinary infection. Hemoglobin levels were between 11.1 and 16 g/dL. Only one case (7.7%) was symptomatic, with mild pharyngeal pain. No vertical transmission was detected by IgM/IgG for SARS-CoV-2. Clinical evolution was favorable in the thirteen cases and they were discharged after 2 to 4 days hospitalization to continue home quarantine. Conclusions: Results in this short study show pregnant women in labor with COVID-19 by rapid IgM test for SARS-CoV-2 at high altitude were mostly asymptomatic; there was no vertical transmission, but high presence of other obstetrical complications.